(untitled) (Damu Journal of Sport Sciences, 2025)
The study aimed to investigate the impact of a comprehensive instructional design through educational units aimed at developing students' performance in basic skills, including the overhand serve and court defense. The research problem was identified through the volleyball specialty. Weaknesses in the skills of serving and court defense were identified. In order to master these two skills, the researcher proceeded through the instructional units and a comprehensive instructional design to master these two important skills, and to ensure that students master them. Second-year students in the College of Physical Education and Sports Sciences at Al-Qasim Green University formed the research population and sample. The study involved twenty-four students for the 2024-2025 academic year. Using an experimental approach and consistent with the study's objectives, the researcher concluded that comprehensive educational design positively impacts students' development of the skills of overhand serve (tennis) and court defense. He recommends applying this approach across all age groups to prepare a generation proficient in these two skills.